A strategy for addicting transgene-free bacteria to synthetic modified metabolites - Kato, Yusuke (Frontiers in Microbiology, 2023)
Biological containment is a safeguard technology to prevent uncontrolled proliferation of "useful but dangerous" microbes. Addiction to synthetic chemicals is ideal for biological containment, but this currently requires introduction of transgenes containing synthetic genetic elements for which environmental diffusion has to be prevented. Here, I designed a strategy for addicting transgene-free bacteria to synthetic modified metabolites, in which the target organism that can neither produce an essential metabolite nor use the extracellularly supplied metabolite, is rescued by a synthetic derivative that is taken up from a medium and converted into the metabolite in the cell. Because design of the synthetic modified metabolite is the key technology, our strategy differs distinctly from conventional biological containment, which mainly depends on genetic manipulation of the target microorganisms. Our strategy is particularly promising for containment of non-genetically modified organisms such as pathogens and live vaccines.